The Effect of Firm Specific Variables on Stock Returns of Nepalese Banks - Dangol, Jeetendra; Acharya, Bidhan (Journal of Balkumari College, 2020)
This study focuses to examine the firm specific fundamental variables impact on the stock returns in the context of Nepali banks. The study uses cross sectional panel data of 12 banks for the duration of ten years. The study finds the existence a negative relationship between stock returns (total yield) and firm size. Likewise, the study shows that the book to market equity has negative relationship with stock returns. However, the study reveals that the relationship of earnings yield and cash flow yield with the stock returns is contradicted in comparison to previous studies.